A rare complication of MRSA lid abscess and orbital abscess following strabismus surgery in a child - Teow, Kenneth Kheng Leong; Nor Akmal B,; Jamalia R,; Safinaz Mohd Khialdin, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
Strabismus is one of the most common ocular problems affecting the preschool population and the aim of strabismus surgery is to correct abnormal alignment of the eyes. A 5-year-old girl with strabismus underwent an uneventful surgery and was discharged on the same day with topical medications. Two days later, she returned with a painful right lower eyelid swelling, eye discharge and fever which started 1 day post-surgery. She was admitted for intravenous (IV) antibiotic. Symptoms initially improved after 24 hours of treatment, but later she had worsening eyelid swelling. An urgent CT scan of the orbit showed a right lower lid abscess with orbital cellulitis. Subsequently an examination under anaesthesia (EUA) and incision and drainage (I&D) of the lower lid abscess were performed. Culture from the pus grew Community Acquired Methicillin-resistant Staphylococcus aureus (CA-MRSA), sensitive to Vancomycin. At day 2 post I&D she subsequently developed another episode of localised right lower lid swelling. Another EUA was done but showed the lower lid and wound was free of pus. She was later found to have a toxic reaction to topical Gentamicin and hence this medication was stopped. She responded well to treatment and was discharged after completing her IV antibiotics. At 14 months outpatient follow up, she was well and orthophoric in primary gaze. While treating a disease, we should be opened to all possibilities and not to treat with multiple antibiotics once susceptibility is known.